Legalitas Komersialisasi Fanart Anime - Jessy Wijaya; Yudi Kornelis (Widya Yuridika, 2022)
The popularity of anime makes fans take an active role in their community, one of them is by commercializing anime fanart. The commercialization of anime fanart is rather an ambiguous problem, considering that there is no specific regulation about this matter, either in the Law No. 28 of 2014 on Copyright or Japan Copyright Act. The commercialization of anime fanart occurs because fan artists do not understand this matter. Anime fanart is a work produced by fan artist’s creativity with their own style as an element of originality and differentiating them from the original creator and other fan artist’s work, but on the other hand, anime fanart used pre-existing anime characters as their fanart inspiration. Fanart as a work that has elements of originality but not completely original make commercializing anime fanart an act that does not violate the rules. The purpose of this study is to compare the commercialization of anime fanart regulation between Indonesia and Japan. This study uses a normative juridical research method with a comparative law approach and a statute approach. The result of this study indicates that the commercialization of anime fanart has been implicitly regulated in Indonesia Copyright Act, as well as in Japan Copyright Act. In addition, Law No. 28 of 2014 on Copyright and Japan Copyright Act, both categorized the commercialization of anime fanart as an act of copyright infringement.